Design and analysis of redundant binary booth multipliers - He, Ya Juan (2010)
Multiplication is a fundamental operation in most arithmetic computing systems. Over the last few decades, Redundant Binary (RB) number has emerged as a key internal format to speed up the partial product accumulation of treestructured parallel multipliers due to its carry-free property and regularity in Very Large Scale Integrated (VLSI) implementation. In this thesis, the high performance energy-efficient multiplication operation has been investigated based on three key constituent components of the RB Booth multiplier architecture.